(untitled) (Communication & Society, 2023)
How much do the performances of top candidates in televised debates affect vote intentions in parliamentary democracies? The article addresses this question and disentangles the effects of predisposition and performance in televised debate reception. Drawing on a large-N field study of the 2017 chancellor duel in Germany, which contains survey and real-time response data for 5660 participants, we identify debate-induced determinants of shifts in voting intention and assess their relative effect sizes on such changes. Our analysis shows, first, that out-party identification is an effective barrier against shifts in voting intentions. However, we find that viewers’ real-time performance perceptions of the candidates show strong effects. Third, we demonstrate that these real-time evaluations can breach the predisposition’s barrier particularly when the intensity of out-party identification is less than very strong. Fourth, we find verdicts on the debate winner as an additional short-term factor that can foster shifts in voting intentions in the course of debate reception. Overall, our results indicate that pre-dispositions may hinder rational updating of electoral behaviour but that debate performance can actually make a difference by altering the formation of voting intentions.